FIRE SAFETY ISSUES AND WAYS TO SOLVE THEM - M.Doschanov; O.Yuldosheva (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides information on fire safety problems and their causes. There are also suggestions and tasks to address these issues